Head control and head-trunk coordination as a function of anticipation in sidestepping - Zeff, S.; Weir, G.; Hamill, J.; van Emmerik, R. (Journal of Sports Sciences, 2022)
Head reorientation precedes body reorientation during direction change to facilitate gaze realignment, thus enhancing perceptual awareness. Whole body kinematics are dependent on the available planning time. The purpose of this study was to assess the role of anticipation on head control and head-trunk coordination during sidestepping tasks. Fourteen male collegiate athletes performed anticipated and unanticipated sidestepping tasks. Transverse plane head, trunk and heading direction, as well as head-trunk coordination were assessed. During change of direction tasks, we observed greater head orientation towards the new travel direction, followed by heading direction and then trunk direction during both anticipated and unanticipated tasks. With reduced planning time, heading in the preparatory phase and trunk rotation in the preparatory and stance phases were significantly less oriented towards the new travel direction, with no differences in head rotation. During anticipated sidestepping, significantly greater in-phase coordination was observed during the preparatory phase compared to unanticipated sidestepping. Head reorientation facilitates gaze realignment and may be prioritized irrespective of planning time during sidestepping tasks. During anticipated trials, the head and trunk move more synchronously compared to unanticipated sidestepping, highlighting the potential benefits of aligning the degrees of freedom earlier in the change of direction stride and optimizing perceptual awareness.